Comparative Evaluation of Efficacy of Self-Assembling Peptide (P11-4), Bioactive Glass, and Arginine Bicarbonate Remineralizing Agents on Simulated Carious Lesion - Rashmi P Yadahalli; Yazeed Abdullah Alotaibi; Ravinder Singh; Mohammed Najmuddin; Mohamed Tharwat Salama; Radha Prasanna Dalai; Noura Alessa; Vardarajula Venkat Ramaiah (Journal of Pharmacy and Bioallied Sciences)
Objectives: Evaluation of effectiveness of bioactive glass, self-assembling peptide (P11-4), and arginine bicarbonate remineralizing agents on simulated carious lesion. Material and Methods: This research was conducted using 40 human premolar teeth that had just been removed. Remineralization of demineralized teeth was carried out three times a day for 14 days for 5 minutes using the appropriate remineralizing agents (Group A: calcium sodium phosphosilicate (bioactive glass), Group B: self-assembling peptide (P11-4), Group C: arginine bicarbonate remineralizing agents, and control group: Group D: deionized water). Using the Vickers hardness number, the degree of demineralization and remineralization was assessed. Results: In every group, there was a drop in microhardness from the baseline to demineralization. In all three test groups, the shift in microhardness values from demineralization to remineralization was shown to be statistically significant. Conclusion: Higher remineralizing capacity was found in bioactive glass and self-assembling peptide (P11-4), which can be employed therapeutically to treat early carious lesions.